2010
DOI: 10.1039/c005387m
|View full text |Cite
|
Sign up to set email alerts
|

Free cadmium ions released from CdTe-based nanoparticles and their cytotoxicity on Phaeodactylum tricornutum

Abstract: The risk of nanoparticles (NPs) to organisms and the environment has become more noticeable alongside their rapid applications in many fields. The release of Cd(2+) from CdTe-based NPs (CdTe-NPs), an important class of engineered nanomaterials, is one of the possible factors responsible for the cytotoxicity of these NPs. Based on the same CdTe core, CdTe/CdS, CdTe/ZnS and CdTe/SiO(2) NPs were synthesized and their Cd(2+) release rates were carefully studied based on dialysis using inductively coupled plasma ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…Indeed, other authors have attributed observed toxicity to metal ions leaching from the QDs core [34,[70][71][72][73]. Similar results were also reported by Benavides et al [11] after exposing C. auratus to AlO 3 and ZnO nanoparticles (NPs).…”
Section: Discussionsupporting
confidence: 74%
“…Indeed, other authors have attributed observed toxicity to metal ions leaching from the QDs core [34,[70][71][72][73]. Similar results were also reported by Benavides et al [11] after exposing C. auratus to AlO 3 and ZnO nanoparticles (NPs).…”
Section: Discussionsupporting
confidence: 74%
“…After they were exposed to CdSe/ZnS‐QDs capped by mercaptoacetic acid and 2‐mercaptopropionic acid, respectively, they observed that core/shell QDs could hardly be internalized into the plant but only were adsorbed on the plant surface. In contrast, Phaeodactylum tricornutum and rice can not only absorb the ions released by QDs but also internalize entire QDs [20,24] . However, the difference of the surface coating of QDs significantly affects the internalization of the same plant.…”
Section: Interaction Between Qds and Plantsmentioning
confidence: 99%
“…The uptake of QDs mainly includes two approaches, i) directly adsorbed by plants as particles; ii) the ions released by QDs were taken up by plants. Researchers usually reveal the uptake and accumulation of QDs by plants through fluorescence microscope, confocal microscope, inductively coupled plasma mass spectrometry, or Raman spectroscopy [18–21] . But to date, whether QDs can completely be internalized by plants is not well elucidated.…”
Section: Interaction Between Qds and Plantsmentioning
confidence: 99%
“…Alternatives such as environmental SEM/TEM which do not require vacuum in the specimen chamber and thus do not require a dry sample are currently being refi ned. Fluorescence or preferably confocal laser scanning microscopy (CLSM) are valuable to visualize fl uorescent NMs [ 48 ]. Depending on the fl uorescence wavelength emitted by the NMs, algal autofl uorescence may interfere with NM detection.…”
Section: Testing Nanomaterials Toxicity In Unicellular Eukaryotic Algamentioning
confidence: 99%